Answer:
In the problem, the sum of the two functions is 2x + 2
Step-by-step explanation:
For this problem, we have to add together f(x) and g(x).
<em>f(x) = 9 - 3x</em>
<em>g(x) = 5x - 7</em>
(f + g)(x) = (9 - 3x) + (5x - 7)
Combine like terms.
(f + g)(x) = 2x + 2
So, when you combine the two functions together, you will get 2x + 2.
If you would like to solve p = r - c for c, you can do this using the following steps:
p = r - c /+c
p + c = r - c + c
p + c = r /-p
p + c - p = r - p
c = r - p
The correct result would be c = r - p.
Well,
First solve the square root which is 7
Funny enough, this makes 7 * 7 = 49
So the answer is 49!
Hope I helped!
What triangle?? can you be more specific?